Whose Discourse Is It Anyway? Understanding Resistance through the Rise of "Barstool Biology" in Nature Conservation. Issue 4 (4th July 2017) - von Essen, Erica
Abstract : This study examines what happens when contentious lay citizens harness the technical-ecological repertoire of experts as means of challenging nature conservation policy. The causes, manifestations, and implications of this phenomenon are elucidated through a critical discourse analysis. The case study is based on the wolf reintroduction project in Europe, with particular focus on Sweden, using illegal hunting discussions as a point of entry within the hunting community. It reveals the deployment of three topoi, which are defined as stock arguments situated within a discourse. Analysis shows how while some topoi often incur short-term gains in the debate because of their scientific guise, they are fundamentally relegated as folk science (or "barstool biology") by government experts and, in some cases, contribute to the further marginalization of other knowledges. Acquiescence to this discourse is shown to greatly impede the debate. Finally, the study shows how lack of trust in the public dialog, which hunters openly recognize to be colonized by ecological expertise, results in increasingly noncommunicative forms of resistance toward policy.